The Impact of Word of Mouth and Brand Image on Purchase Decisions of the Tanjung Priok Branch Courier Company - Sekar Widyastuti Pratiwi; Sesaria Mardhiani Rachma Puspita; Adit Taufiqurrahman; Radifan Fadhli Prasetyo (Dinasti Review, 2025)
This study examines the effect of word of mouth and brand image on purchasing decisions for courier companies. The population of this study were users of Indah Logistik Cargo services in the Tanjung Priok branch. The sampling technique used is random sampling which has been determined by the researcher using Hair's formula, namely 108 service users of Indah Logistik Cargo, Tanjung Priok branch. Using a survey instrument and survey methodology, data was gathered. The technique for analyzing the data is multiple regression analysis. Statistical testing is done in two ways: partial testing (t-test) and simultaneous testing (f-test). Word of mouth had a partial positive effect and a significant impact on purchasing decisions, according to the results. Purchasing decisions are positively and significantly impacted by brand image. Word-of-mouth and brand image have a substantial and considerable impact on purchasing decisions at the same time, independent of each other.